If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(X-6)-(3X+2)=4(2X+2)
We move all terms to the left:
(X-6)-(3X+2)-(4(2X+2))=0
We get rid of parentheses
X-3X-(4(2X+2))-6-2=0
We calculate terms in parentheses: -(4(2X+2)), so:We add all the numbers together, and all the variables
4(2X+2)
We multiply parentheses
8X+8
Back to the equation:
-(8X+8)
-2X-(8X+8)-8=0
We get rid of parentheses
-2X-8X-8-8=0
We add all the numbers together, and all the variables
-10X-16=0
We move all terms containing X to the left, all other terms to the right
-10X=16
X=16/-10
X=-1+3/5
| 16h^2+8=-12 | | 5^x=5^{3x-2} | | 9(4x-8)-(x+3)=(x+9)5 | | 5x+3=-x-7+4x | | 11^(6x+2)=12 | | 4x(2)-64=0 | | 6y+4=4.4 | | 4x(×+3)=12 | | y=15000(1.04)^25 | | y=15000(1.04)²⁵ | | y/5-11=24 | | u/3+14=25 | | 9x+10=-5x+158 | | (Y-18)(8y+16)=0 | | 4x^2-44x=20x+252 | | 200=100-25a | | 2a+0.6=1.4 | | -6=-4+a | | c(C-64)=0 | | 3q^2-4q=55 | | 3m(m-4)=21 | | -919x^2-600=-600 | | 792x^2+97=180 | | 3f+9ff=4 | | -799x^2-297=-218 | | -x^2+361=0 | | 7x+8=5x0 | | 15x+9=8x+44 | | 10x-9=3x-44 | | 2=1.015^4x | | 2(3-h)-6=(-5h) | | 2(4x-3)=3x-11 |